Strengthening Community Awareness of Communicable and Non-Communicable Diseases through Education for Sustainable Development to Promote Healthy and Independent Villages - Giyantolin; Dody Indra Sumantiawan; Aerrosa Murenda Mayadilanuari; Silvia Nurvita (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service activity aims to increase public knowledge and awareness of infectious and non-infectious diseases as part of efforts to establish an ESD-based Healthy Independent Village in Muktiharjo Kidul Village, Semarang City. The methods employed included health education and awareness campaigns through interactive outreach sessions conducted in collaboration with the Semarang City Health Department, case discussions, post-activity questionnaires, and the distribution of educational pamphlets containing information on disease types, risk factors, and preventive measures for both infectious and non-infectious diseases. The activity was evaluated using quantitative and qualitative descriptive analysis techniques. The results indicated strong support from the village government regarding program sustainability, as well as high levels of community enthusiasm toward the activities. Initial assessments showed that the knowledge levels of health cadres varied considerably, with notable gaps in several topics, particularly scabies (14.89%) and leptospirosis. Following the educational intervention, the community demonstrated positive responses, active participation, and increased awareness of the importance of behavior- and environment-based disease prevention. In addition, the activity produced educational pamphlets that were used as tools for disseminating information at the family and community levels. The ESD approach also encouraged the active involvement of health cadres as agents of change in supporting the sustainability of community-based health programs.